Vulnerable neoatherosclerosis in coronary artery with whole circumference showing intravascular echo attenuation. Issue 5 (23rd April 2019) - Hirota, Yukiho; Nomura, Tetsuya; Ono, Kenshi; Sakaue, Yu; Ueno, Daisuke; Hori, Yusuke; Yoshioka, Kenichi; Kikai, Masakazu; Keira, Natsuya; Tatsumi, Tetsuya
Key Clinical Message: Neoatherosclerosis is emerging as a stent‐associated problem that has not yet been fully resolved. Because in‐stent restenosis with a neoatherosclerotic etiology is associated with a high risk of acute coronary syndrome and a poor survival prognosis, it is essential to precisely identify patients at risk using advanced imaging modalities. Abstract : Neoatherosclerosis is emerging as a stent‐associated problem that has not yet been fully resolved. Because in‐stent restenosis with a neoatherosclerotic etiology is associated with a high risk of acute coronary syndrome and a poor survival prognosis, it is essential to precisely identify patients at risk using advanced imaging modalities.